2011
DOI: 10.1186/1477-5956-9-37
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteins regulated by heat stress in rice leaves

Abstract: BackgroundHigh temperature is a critical abiotic stress that reduces crop yield and quality. Rice (Oryza sativa L.) plants remodel their proteomes in response to high temperature stress. Moreover, phosphorylation is the most common form of protein post-translational modification (PTM). However, the differential expression of phosphoproteins induced by heat in rice remains unexplored.MethodsPhosphoprotein in the leaves of rice under heat stress were displayed using two-dimensional electrophoresis (2-DE) and Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 38 publications
5
28
0
Order By: Relevance
“…Replacing the hydrophobic Phe by a charged residue in this interface should impede the interaction in the dimer–dimer interface and stabilize the dimeric form (F84R). Recently, it was found that Oryza sativa 2-CysPrx is phosphorylated (Chen et al , 2011). Plant 2-CysPrxs have the conserved threonine residue T92.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Replacing the hydrophobic Phe by a charged residue in this interface should impede the interaction in the dimer–dimer interface and stabilize the dimeric form (F84R). Recently, it was found that Oryza sativa 2-CysPrx is phosphorylated (Chen et al , 2011). Plant 2-CysPrxs have the conserved threonine residue T92.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, previous studies have suggested that pH, temperature, and salt concentrations influence the conformation (Bernier-Villamor et al , 2004). In a proteomics approach, rice 2-CysPrx was detected as being reversibly phosphorylated, with heat as the trigger of dephosphorylation (Chen et al , 2011). Introduction of a negative charge at Thr92 mimicking phosphorylation increased the sensitivity of 2-CysPrx to hyperoxidation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the detection limit of Pro-Q Diamond is as low as a few ng [28]. Second, specificity of Pro-Q Diamond staining was directly confirmed by comparing non-dephosphorylated and dephosphorylated samples or by comparison with autoradiograms after 32 P-labeling of samples [29][30][31][32][33]. Third, our preliminary experiments showed that band patterns in 1D-gels revealed by Pro-Q Diamond staining correspond to those revealed by immunoblots against P-Ser, P-Tyr and P-Thr (not shown).…”
Section: The Cardiac (Phospho)proteome As Revealed By 2d Gel Electropmentioning
confidence: 99%
“…Three independent sets of ontologies were used to describe a gene product, the biological process, the molecular function and the cellular compartment (Chen et al 2011).…”
Section: Gene Ontology (Go) Analysismentioning
confidence: 99%